Disulfide Cross-linked Micelles for the Targeted Delivery of Vincristine to B-cell Lymphoma - Kato, Jason (Mol Pharm, 2012)
Vincristine (VCR) is a potent anti-cancer drug but its clinical efficacy is dose-limited by severe neurotoxicity. Prophylactic and palliative treatment of VCR-induced toxicity have been explored without significant findings. The field of drug delivery may provide an opportunity to increase the therapeutic index of VCR by delivering the drug specifically to tumor sites while sparing normal tissue. We have recently developed a telodendrimer (PEG(5k)-Cys(4)-L(8)-CA(8)) capable of forming disulfide cross-linked micelles which can encapsulate a variety of chemotherapeutics. In the present study, we encapsulate VCR into these micelles (DCM-VCR) and use them to treat lymphoma bearing mice. DCM-VCR particles have a size of 16 nm which is ideal for tumor accumulation via the enhanced permeability and retention (EPR) effect. Compared to our first-generation non-cross-linked micelles, DCM-VCR demonstrated greater stability and slower drug release in physiological conditions. In addition, DCM-VCR exhibited an MTD of 3.5 mg/kg while the MTD for conventional VCR was only 1.5 mg/kg. Using a NIRF dye, we showed that DCM-VCR accumulated at the tumor site starting 1 h after injection and persisted up to 72 h in lymphoma bearing mice. In an in vivo efficacy study, high dose (2.5 mg/kg) DCM-VCR exhibited the greatest reduction in tumor volume. High dose DCM-VCR was well tolerated and did not cause additional toxicity as measured by body weight, complete blood count, serum chemistry and histological analyses of the sciatic nerve. Mice treated with equivalent concentrations (1 mg/kg) of conventional VCR and DCM-VCR controlled tumor growth equally, however, in combination with on-demand addition of the reducing agent, N-acetylcysteine, DCM-VCR exhibited a superior anti-tumor effect compared to conventional VCR.